2017
DOI: 10.11648/j.iji.20170501.13
|View full text |Cite
|
Sign up to set email alerts
|

Polio Eradication in Bangladesh: Evaluation of AFP Surveillance Indicators, 2011-2015

Abstract: Abstract:As per recommendation from WHO, Bangladesh began a comprehensive plan for AFP (Acute Flaccid Paralysis) and EPI (Expanded Program on Immunisation) disease surveillance from 1997. The country has been maintaining key performance indicators for AFP surveillance for the past ten years. Bangladesh has been declared polio free on 27 th March 2014. The aim of this paper is to evaluate and describe results of AFP surveillance indicators for Bangladesh showing the progress made over time as well as identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
3
8
0
Order By: Relevance
“…However, importation of poliovirus remains a potential threat; therefore, it is essential to continue AFP surveillance. The study reported that half of the reported cases were of patients below 5 years of age, which is consistent with findings of a study conducted in Iran [10] and another one in Bangladesh [11]. However, higher percentages were reported in countries such as Congo (85.2%) [12] and Ghana (74.4%) [13], and lower percentages were reported in other countries including Italy (37%) [14].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, importation of poliovirus remains a potential threat; therefore, it is essential to continue AFP surveillance. The study reported that half of the reported cases were of patients below 5 years of age, which is consistent with findings of a study conducted in Iran [10] and another one in Bangladesh [11]. However, higher percentages were reported in countries such as Congo (85.2%) [12] and Ghana (74.4%) [13], and lower percentages were reported in other countries including Italy (37%) [14].…”
Section: Discussionsupporting
confidence: 84%
“…This impressive vaccination coverage is explained by the repetitive campaigns conducted in 2013-2016 that targeted prevention of polio importation from Syrian refugees and the high awareness of parents to ensure completion of the vaccination schedule and taking recommended doses during campaigns. A similar finding was revealed in Bangladesh (75%) [11]. In Turkey, 84.5% of the studied cases had at least one oral polio vaccine dose [15].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The ndings that most (51%) reported AFP cases were <5 years is signi cant and implies that the surveillance system could have detected WPV or cVDPV (if it was present) since poliomyelitis commonly affect children within this age group 19 . Similarly, other studies that evaluated AFP surveillance systems also found that most AFP cases were in children less than 5 years in Nigeria (82%) 2 , Ghana (76%) 3 , Ethiopia (68%) 20 , Iran (53%) 21 , Bangladesh (54%) 22 , and Democratic Republic of the Congo (85%) 23 .…”
Section: Discussionmentioning
confidence: 62%